2013
DOI: 10.1002/jgrd.50817
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and organic nitrates over the eastern United States: Sensitivity to isoprene chemistry

Abstract: [1] We implement a new isoprene oxidation mechanism in a global 3-D chemical transport model (GEOS-Chem). Model results are evaluated with observations for ozone, isoprene oxidation products, and related species from the International Consortium for Atmospheric Research on Transport and Transformation aircraft campaign over the eastern United States in summer 2004. The model achieves an unbiased simulation of ozone in the boundary layer and the free troposphere, reflecting canceling effects from recent model u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
326
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 296 publications
(342 citation statements)
references
References 143 publications
(226 reference statements)
15
326
1
Order By: Relevance
“…The two limits converge for smaller compounds (<80 Da) with high diffusivity such that r s is minimal. As expected, the observed daytime V d for HNO 3 (the prototypical molecule for rapid deposition) is at maximum for its size. It appears that bulkier compounds such as MTNP cannot achieve surface resistance-free deposition because they are hindered by subsequent transport through the stomata.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The two limits converge for smaller compounds (<80 Da) with high diffusivity such that r s is minimal. As expected, the observed daytime V d for HNO 3 (the prototypical molecule for rapid deposition) is at maximum for its size. It appears that bulkier compounds such as MTNP cannot achieve surface resistance-free deposition because they are hindered by subsequent transport through the stomata.…”
Section: Resultssupporting
confidence: 78%
“…Due to its high emission and fast reactivity, the atmospheric oxidation of isoprene significantly impacts air quality and climate by altering the regional and global budgets of organic aerosols (2) and oxidants [e.g., ozone (3) and HO x = OH + HO 2 (4)]. Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…SI Appendix, The chemical mechanism is adopted from GEOS-Chem v9.1 with updates on chemistry of aromatics (47), isoprene (54,55), and isoprene nitrates (56)(57)(58). It is noteworthy that recent studies (58) found that field measurements are consistent with relatively low NO x recycling efficiency (∼25%), resulting mainly from aerosol uptake, indicating that the impact of isoprene nitrate chemistry on surface ozone is much smaller than previously thought (56). With these updates, we find that the impact of isoprene nitrate chemistry is less than 1 ppbv regionally.…”
Section: Methodsmentioning
confidence: 99%